Wanita di Mata Media Indonesia (analisis Wacana Kritis Sara Mills pada Berita Online) - Robaeti, Enur; Hamdani, Agus (Titian: Jurnal Ilmu Humaniora, 2023)
This study focuses on sexual violence against women in the context of online media coverage. Ethical media is expected to present information with objectivity and balance. Various reports on sexual harassment frequently experienced by women represent individuals within a discourse. Currently, the exploitation of women is carried out in more intellectual and visually appealing ways, including through the discourse expressed in mass media. In the media, women are often given prominent visual emphasis, while their true meaning is often overlooked. If this continues, it will further reinforce gender disparities between women and men, potentially increasing the oppression faced by women. The problem addressed in this research is the discourse analysis using Sara Mills' theory. Sara Mills focuses her discourse theory discussion on feminist issues, including how women are portrayed in the news. The research method employed is a literature review. Based on the findings of this study, it can be concluded that there is bias in the representation of women in news texts across three different media outlets. Abstract Penelitian ini memfokuskan pada kekerasan seksual yang terjadi pada perempuan dalam konteks pemberitaan media bold. Media yang berintegrasi diharapkan mampu menyajikan informasi dengan objektivitas dan keseimbangan. Berbagai laporan mengenai pelecehan seksual yang sering menimpa perempuan merepresentasikan individu dalam suatu wacana. Saat ini, tereksploitasi terhadap perempuan dilakukan dengan cara yang lebih intelektual dan dikemas secara menarik, termasuk melalui wawasan yang sepi dalam media massa. Dalam media, perempuan sering kali diberi penekanan visual yang menonjol, namun makna yang sebenarnya seringkali terabaikan. Jika hal ini terus berlanjut, akan semakin memperkuat ketegangan gender antara perempuan dan laki-laki, yang berpotensi meningkatkan penahanan terhadap perempuan. Permasalahan yang dikaji dalam penelitian ini adalah analisis wacana dengan menggunakan teori Sara Mills. Sara Mills memfokuskan pembahasan teori wacana pada isu-isu feminisme, termasuk bagaimana perempuan ditampilkan dalam berita. Metode penelitian yang digunakan adalah studi pustaka. Berdasarkan hasil penelitian ini, artinya terdapat bias dalam representasi perempuan dalam teks berita pada tiga media yang berbeda.